Being a Parent to an Adult Child With Drug Problems : Negative Impacts on Life Situation, Health, and Emotions - Richert, Torkel; Johnson, Björn ; 0000-0002-1601-2706; Svensson, Bengt (Journal of Family Issues, 2018)
This study is about the vulnerability of parents to adult children with drug problems. The study is based on a self-reporting questionnaire (n = 687) distributed to parents in Sweden via family member organizations, treatment centers, and online communities. Most parents reported extensive negative consequences on relationships, social life, and mental health due to their children’s drug problems. Most parents also experienced strong feelings of powerlessness, grief, guilt, and shame. Many parents reported a negative impact on their economy and work ability. In general, fathers claimed to feel less of a negative impact than mothers. A more severe drug problem and life situation for the child was associated with a greater negative impact for the parents. Many parents experienced difficulties in securing adequate help both for their child and for themselves. The study shows the need for increased support efforts for this parent group.
2024-02-05T14:50:54.972+01:00
Keywords: parents; adult children; drug problems; vulnerability; family health; family burden; shame; Social Sciences; Samhällsvetenskap